Reconstruction of the fetus face from three-dimensional ultrasound using a newborn face statistical shape model. (June 2022) - Alomar, Antonia; Morales, Araceli; Vellvé, Kilian; Porras, Antonio R.; Crispi, Fatima; Linguraru, Marius George; Piella, Gemma; Sukno, Federico
Abstract: Background and objective: The fetal face is an essential source of information in the assessment of congenital malformations and neurological anomalies. Disturbance in early stages of development can lead to a wide range of effects, from subtle changes in facial and neurological features to characteristic facial shapes observed in craniofacial syndromes. Three-dimensional ultrasound (3D US) can provide more detailed information about the facial morphology of the fetus than the conventional 2D US, but its use for pre-natal diagnosis is challenging due to imaging noise, fetal movements, limited field-of-view, low soft-tissue contrast, and occlusions. Methods: In this paper, we propose the use of a novel statistical morphable model of newborn faces, the BabyFM, for fetal face reconstruction from 3D US images. We test the feasibility of using newborn statistics to accurately reconstruct fetal faces by fitting the regularized morphable model to the noisy 3D US images. Results: The results indicate that the reconstructions are quite accurate in the central-face and less reliable in the lateral regions (mean point-to-surface error of 2.35 mm vs 4.86 mm). The algorithm is able to reconstruct the whole facial morphology of babies from US scans while handle adverse conditions (e.g. missing parts, noisy data). Conclusions: The proposed algorithm has the potential to aid in-utero diagnosis for conditions that involve facial dysmorphology.